(untitled) (Nigerian Journal of Technology, 2024)
Many applications require variable speed operation. The motor speed needs to be controlled to save more power. It became highly imperative for further research to find out an efficient method that can yield an optimal speed control. This study presents the design and modeling of a proportional derivative controller for a three-phase induction motor speed control. The scalar control methodology was used to investigate the performance of motor speed control. For the controller approach, proportional-integral (PI) and proportional-derivative (PD) controllers were investigated. Simulation results using MATLAB (Simulink) software is presented. Furthermore, investigation of the PI, and PD performance shows that the PI controller performed poorly due to existence of high peaks, overshoots and rise time. However, the PD controller yielded satisfactory results. Hence, PD controller revealed a better performance with a 1.01s settling time and a steady state error of 1.0 as against that of the PI controller which was unstable, an overshoot of approximately 96% and a steady state error of 1.22.